Pengaruh Promosi dan Kualitas Pelayanan Terhadap Minat Menabung Nasabah Pada PT. BPR Gema Pesisir - Alfian Alfian; Santika Apriliana (CV. Ulil Albab Corp, 2022)
The purpose of this study was to determine the effect of promotion and service quality on customer interest in saving at PT. BPR Gema Pesisir The population in this study were all customers of PT. BPR Gema Pesisir Determining the sample using the Slovin formula, the number of respondents as a sample in this study was 89 customers. The data analysis technique used to test the hypothesis is statistical t test. The results showed that Promotion, Tangible,Empathy, Reliability, Responsiviness, and Assurance had a significant effect on customer interest in saving at PT. BPR Gema Pesisir This is because promotion, tangible,empathy, reliability, responsiveness, and assurance have a significantly smaller value than alpha 0.05.